Credit frictions, selection into external finance and gains from trade - Florian Unger (Canadian Journal of Economics/Revue canadienne d'économique, 2021)
This paper analyzes the effects of credit frictions in a trade model where heterogeneous firms select both into exporting and into two types of external finance. While small producers face stronger credit frictions and rely on bank finance, large firms have access to cheaper bond finance. The analysis shows that a bank credit shock leads to an increase in the share of firms that use bond finance. This selection effect is used to explain the observed decrease in bank finance relative to bond finance during the global financial crisis of 2007–2009. A calibration of the model to the crisis period documents that endogenous selection into external finance reduces the negative implications of credit frictions on product variety, exports and gains from trade.
Keywords: 330